Pemanfaatan E-Commerce dan Sistem Informasi Akuntansi Pada Usaha UMKM Pasca Pandemi Covid 19 Di Desa Dukuh Dempok, Kec. Wuluhan, Jember - Riyanto Setiawan Suharsono; Naely Azhad; Budi Santoso (DIKEMAS (Jurnal Pengabdian Kepada Masyarakat), 2022)
The development of science and technology through the use of E-Commerce and Accounting Information Systems in the business world, especially in Micro, Small and Medium Enterprises (MSMEs) has increased in recent years. E-Commerce which is a buying and selling activity through electronic media allows it to be carried out by business actors and the public even though they have limited capital. The financing network, business network as well as MSME business competition which are quite extensive and growing also require adequate Accounting Information System facilities to collect transaction data, make decisions and supervise the organization. The ability to absorb labor from MSMEs is also quite large. This makes MSMEs have an important role in the economy of a region. The emergence of the Covid-19 Pandemic in early 2020, whose impact is still being felt in 2021, has raised various problems due to reduced income for most people in general. All MSME sectors are affected by the Covid-19 Pandemic. For this reason, innovations are needed in increasing people's income through the use of E-Commerce and Accounting Information Systems to increase the business potential of MSMEs. This Service Program seeks to provide answers and solutions to problems faced by some small communities and MSME business actors who are affected by the Covid-19 Pandemic and are not familiar with technological developments. Based on the problems faced by the community, the service that will be carried out is to provide training and education to the community and MSME actors in Dukuh Dempok Village, Kec. Wuluhan, Jember. This community service method uses seminars/workshops, practices and discussions with MSME actors in Dukuh Dempok Village, Kec. Wuluhan, Jember